P072 Circadian misalignment by simulated night shifts decreases colonoid barrier integrity in Ulcerative Colitis. (30th January 2023) - Swanson, G; Shaikh, M; Keshavarzian, A; Scheer, F
Abstract: Background: Circadian rhythms orchestrate multiple biological processes with 24-hour oscillations that regulate diverse bodily functions. The central clock is in the suprachiasmatic nucleus and orchestrates peripheral circadian clocks in every organ system including the gastrointestinal tract (GIT). Previous work has shown that circadian misalignment in Ulcerative Colitis (UC) is associated with increased colonic permeability, and colonic organoids recapitulate the host circadian phenotype. The goals of this study were to examine whether circadian misalignment would disrupt the colonic barrier integrity in UC. Methods: 5 subjects, 2 UC and 3 Healthy Controls (HC), were recruited into the study. All UC subjects were inactive (partial Mayo Score ≤ 1) and stable medications with no flares for the last 3 months. For two weeks prior to entry into the circadian lab all subjects were on a prescribed regular sleep schedule. Subjects were then kept in the circadian lab for 6 days with strict control of their light/dark cycle (Figure 1). All subjects then underwent two unprepped flexible sigmoidoscopies at: (1) baseline with circadian alignment and (2) after three days of simulated night shifts with circadian misalignment. Colonic organoids generated created from the colon tissue biopsies grown in Matrigel and barrier integrity was assessed in apical-out colonoids by FITC-Dextran (4 kDa) Net Fluorescence was estimated by ImageJ. Results: Colonic organoids at baseline had significantly decreased ZO-1 in UC versus HC, Figure 2. At baseline there was an increase in UC colonic organoid barrier integrity as measured by net fluorescence (density/area). In UC vs HC barrier integrity was 855 ± 203.8 vs 333.1 ± 52.9, p<0.05. After three days of simulated night shifts, barrier integrity significantly increased in both groups at was 1100 ± 342 vs 656 ± 197.9, p <0.5 (Figure 3). After 24 hours of treatment with cytokines, barrier integrity in HC, UC, misaligned HC, and misaligned UC was 2227 ± 376, 2030 ± 264, 1787 ± 402, and 1506 ± 332, (Figure 4). Conclusion: Circadian misalignment by alternation of light:dark cycles (simulated night shift) causes misalignment of host central clock and impacts circadian regulated biological process like tight junction proteins which decreases colonic barrier integrity. This study highlights the importance of studying environmental factors that impact circadian timing in UC including night shift work which may be a significant risk factor for a disease flare. Further in vivo and in vitro studies are ongoing to determine the mechanisms through which circadian misalignment impacts colonic barrier integrity in UC (NCT05180279).